Antibacterial Activity of Tris NaCl and PBS Buffer Protein Extract of Cassia fistula, Saccharum officinarum, Albizia lebbeck and Cymbopogon citrates Against Bacterial Strains. Issue 1 (4th February 2021) - Habiba, Ume; Nisar, Jaweria; Choohan, Muhammad Akram; Shah, Syed Muhammad Ali; Nisar, Zonaira; Mustafa, Imtiaz
Medicinal plants are gaining popularity over synthetic medicines because antibiotic resistance demands the alternative source of medication. In the present research, the crude protein extraction of 4 medicinal plants Cassia fistula, Saccharum officinarum, Albizia lebbeck and Cymbopogon citrates was carried out. Crude protein extraction was done by 2 different buffers i.e. Tris NaCl buffer and PBS buffer. Protein confirmation was done by Bradford assay in the spectrophotometer. Antibacterial potential was checked and compared against Escherichia coli, Bacillus subtilis, Neisseria gonorrhoea, Bacillus cereus and Proteus mirabilis. Antibacterial assay was performed by disc diffusion method, agar well method and zones of inhibition were calculated. The study results indicated that Tris NaCl extracts' antimicrobial potential is higher than that of the PBS buffer. On disc diffusion method the Tris NaCl buffer extracts of Cymbopogon citrates showed maximum zone of inhibition 11 mm and 9 mm against Bacillus subtilis and Bacillus cereus respectively and control chloramphenicol showed maximum zone of inhibition 26 mm against Bacillus subtilis. Cassia fistula showed maximum zone of inhibition of 7 mm against Bacillus cereus while Saccharum officinarum and Albizia lebbeck didn't show the any antibacterial activity. On the other hand, Protein extracts from PBS buffer didn't show zone of inhibition against any bacteria. Only Albizia lebbeck showed minute zone of inhibition against Neisseria gonorrhea . On well diffusion method, Cassia fistula Tris NaCl protein extract showed the maximum zone of inhibition 20 mm and 18 mm against Proteus mirabilis and Bacillus subtilis respectively. While Albizia lebbeck PBS protein extract showed the maximum zone of inhibition 19 mm and 17 mm against Bacillus subtilis and Bacillus cereus. The results revealed that the protein extract of Albizia lebbeck, Cymbopogon citrates and Cassia fistula can be used tosynthesize antimicrobial drugs to treat the bacterial infections.